Determine the Prevalence of Hepatitis B and C During Pregnancy by Using Machine Learning Algorithm - Naeem, Awad Bin; Senapati, Biswaranjan; Mahadin, Ghayth AL; Ghulaxe, Vivek; Almeida, Friban; Sudman, Sakiul Islam; Ghafoor, Muhammad Imran (International Journal of Intelligent Systems and Applications in Engineering, 2024)
South Punjab has a high frequency of Hepatitis B and C among pregnant women, making it a highly endemic region. Lack of knowledge, drinking tap water, dental procedures, and past surgery all raise the risk of infection. The anticipated model's accuracy is 86.32%. A low socioeconomic position and a history of surgical therapy are also important considerations. Using medical data sets, this research attempted to illustrate the performance of ensemble approaches in identifying Hepatitis infection. Three algorithms were used, and the suggested model was evaluated using data from actual hepatitis patients. The research discovered that 64% of pregnant women in rural regions had Hepatitis B and C, whereas 36% of pregnant women in urban areas had Hepatitis B and C. Hepatitis C was more prevalent in cities than in rural regions. The research underlines the necessity of correct diagnosis in clinical decision support systems, as well as data set compatibility.